Beyond band bending in the WO3/BiVO4 heterojunction: insight from DFT and experiment. Issue 1 (16th November 2018) - Ràfols i Bellés, Carles; Selim, Shababa; Harrison, Nicholas M.; Ahmad, Ehsan A.; Kafizas, Andreas
Abstract : A new approach for the study of photocatalytic heterojunctions based on a layer-by-layer PDOS has been developed. Our combination of experimental and theoretical calculations reveals the importance of interfacial effects when a heterojunction is formed that can dictate the performance of a heterojunction. Abstract : Heterojunction photocatalysts can significantly enhance the efficiency of photocatalytic water splitting. It is well known that the key to such improvements lies at the interfacial region where charge separation occurs. Understanding the origins of this interfacial enhancement can enable the design of better performing water splitting devices. Therefore, in this work, a novel theoretical–experimental approach is developed for the study of photocatalytic heterojunctions using the model system – WO3 /BiVO4, where it has been shown that the quantum efficiency of water splitting can approach unity at certain wavelengths. Our photoelectrochemical measurements of this heterojunction show a significantly enhanced performance over its separate components when illuminated through the BiVO4 side but not the WO3 side. This is indicative of more efficient electron transfer ( i.e. from BiVO4 to WO3 ) than hole transfer ( i.e. from WO3 to BiVO4 ) across the junction. Our classical band bending model of this junction predicts noticeable interfacial barriers, but could not explain the reduced performance under back illumination. Our atomistic model was used to investigate the effect of interfacial reconstructions and chemical interactions on the electronic structure of the system. The model reveals a non-staggered valence band, in contrast to the staggered conduction band, due to strong hybridization of valence band orbitals in both materials across the interface. This non-staggered valence band does not provide an energetic driving force for charge separation for hole transfer ( i.e. from WO3 to BiVO4 under back illumination). Hence, a significant improvement in performance is only observed under front illumination. This combined approach, using both experiment and theory, results in a more complete understanding of a heterojunction photocatalyst system and provides unique insight into the interfacial effects that arise when two semiconductor materials are brought together, going beyond traditional band bending models.